The effects of aspirated thickened water on survival and pulmonary injury in a rabbit model. (21st July 2017) - Nativ‐Zeltzer, Nogah; Kuhn, Maggie A.; Imai, Denise M.; Traslavina, Ryan P.; Domer, Amanda S.; Litts, Juliana K.; Adams, Brett; Belafsky, Peter C.
Abstract : Objectives/Hypothesis: Liquid thickeners are one of the most frequently utilized treatment strategies for persons with oropharyngeal swallowing dysfunction. The effect of commercially available thickeners on lung injury is uncertain. The purpose of this study was to compare the effects of aspiration of water alone, xanthan gum (XG)–thickened water, and cornstarch (CS)‐thickened water on survival and lung morphology in a rabbit model. Study Design: Animal model. Prospective small animal clinical trial. Methods: Adult New Zealand White rabbits (n = 24) were divided into three groups of eight rabbits. The groups underwent 3 consecutive days of 1.5 mL/kg intratracheal instillation of water (n = 8), XG‐thickened water (n = 8), and CS‐thickened water (n = 8). The animals were euthanized on day 4, and survival and pulmonary histopathology were compared between groups. Results: In all, 12.5% of rabbits (n = 8) instilled with CS‐thickened water survived until the endpoint of the study (day 4). All animals instilled with water (n = 8) or XG‐thickened water (n = 8) survived. A mild increase in intra‐alveolar hemorrhage was observed for the animals instilled with CS‐thickened water compared to the other groups ( P  < .05). In the groups that survived to the endpoint of the study, instillation of water thickened with XG resulted in greater pulmonary inflammation, pulmonary interstitial congestion, and alveolar edema than water alone ( P  < .05). Conclusions: These data suggest that 3 consecutive days of 1.5 mg/kg of aspirated CS‐thickened water are fatal, and that XG‐thickened water is more injurious than aspirated water alone. Additional research is necessary to further delineate the dangers of aspirated thickened liquids. Level of Evidence: NA. Laryngoscope, 128:327–331, 2018